LDCT Lung Cancer Screening Eligibility and Use of CT Scans for Lung Cancer among Sexual Minorities - Veliz, Philip (Cancer Epidemiol, 2019)
OBJECTIVE: To compare eligibility for lung cancer screening and receipt of a CT scan for lung cancer among sexual minorities. METHODS: Secondary data analysis of cross-sectional data from older U.S. adults in the Behavioral Risk Factor Surveillance System survey during the 2017 cycle (n=20,685). RESULTS: Rates of eligibility for low-dose helical computed tomography (LDCT) were roughly twice as high among sexual minorities than among heterosexuals (21.1% vs. 11.7%). The odds of gay men and lesbian women indicating eligibility for LDCT screening were four to five times higher when compared to their heterosexual peers. No statistically significant differences were found between sexual minorities and heterosexuals with respect to having a CT scan for lung cancer in the past year. CONCLUSIONS: There are potential sexual-identity-related disparities in the utilization of lung cancer screening among eligible smokers. Interventions are needed to increase awareness and uptake of lung cancer screening in order to detect and manage this common form of cancer in the U.S.